All Roads Lead to Cytosol: Trypanosoma cruzi Multi-Strategic Approach to Invasion - Ferri, Gabriel; Edreira, Martin M. (Frontiers in Cellular and Infection Microbiology, 2021)
T. cruzi has a complex life cycle involving four developmental stages namely, epimastigotes, metacyclic trypomastigotes, amastigotes and bloodstream trypomastigotes. Although trypomastigotes are the infective forms, extracellular amastigotes have also shown the ability to invade host cells. Both stages can invade a broad spectrum of host tissues, in fact, almost any nucleated cell can be the target of infection. To add complexity, the parasite presents high genetic variability with differential characteristics such as infectivity. In this review, we address the several strategies T. cruzi has developed to subvert the host cell signaling machinery in order to gain access to the host cell cytoplasm. Special attention is made to the numerous parasite/host protein interactions and to the set of signaling cascades activated during the formation of a parasite-containing vesicle, the parasitophorous vacuole, from which the parasite escapes to the cytosol, where differentiation and replication take place.